Integrated tactical planning respond to change, increase competitiveness, and reduce costs - Hozack, Rod; Ferguson, Todd; Harman, Stuart; Howarth, Dawn (John Wiley & Sons, Inc., 2021)
"Integrated Tactical Planning is an explanation and description of the Integrated Tactical Planning (ITP) process and its place in an organization, and more importantly, how to keep the executive focusing more time on the strategic horizon and less time in crisis management and the detail. ITP is a cross-functional re-planning process that routinely re-aligns core plans (product, demand, and supply) in the short term (e.g. 13 weeks), that results in more time for senior executives to spend on the strategic horizon, and authorizes the right people, to make the right decisions, at the right time."--
Includes bibliographical references and index. - Online resource; title from digital title page (viewed on March 12, 2021)
Keywords: Business planning